1991
DOI: 10.1200/jco.1991.9.2.295
|View full text |Cite
|
Sign up to set email alerts
|

Epirubicin at two dose levels with prednisolone as treatment for advanced breast cancer: the results of a randomized trial.

Abstract: Two hundred eleven patients with advanced breast cancer were randomized to receive either epirubicin (E) 50 mg/m2 and prednisolone (LEP) or E 100 mg/m2 and prednisolone (HEP). The intended treatment consisted of 16 courses of LEP or eight courses of HEP given at 3-weekly intervals. Reasons for stopping treatment early included progressive disease, stable disease without symptomatic improvement, or severe toxicity deemed intolerable by either the patient or physician. Toxicity was recorded at 3-weekly and respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0
2

Year Published

1994
1994
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(26 citation statements)
references
References 14 publications
2
22
0
2
Order By: Relevance
“…Moreover, retrospective analyses of clinical trials employing the cyclophosphamide, methotrexate and 5-fluorouracil (CMF) or 5-fluorouracil, doxorubicin and cyclophosphamide (FAC) regimens in MBC carried out independently by Hryniuk (1987) and Tannock et al (1988) showed that an increased dose intensity is associated with a better response rate and an increased quality of life. These data have been partially confirmed, at least in terms of response rates, in several clinical investigations on MBC treated with EPI (Hortobagyi, 1990;French Epirubicin Study Group, 1991;Habeshaw et al, 1991;Marschner et al, 1994). For these reasons new regimens containing high-dose EPI have been developed with the aim of improving clinical results with acceptable toxicity (Hortobagyi, 1990;Ferguson et al, 1993;Marschner et al, 1994).…”
mentioning
confidence: 50%
See 1 more Smart Citation
“…Moreover, retrospective analyses of clinical trials employing the cyclophosphamide, methotrexate and 5-fluorouracil (CMF) or 5-fluorouracil, doxorubicin and cyclophosphamide (FAC) regimens in MBC carried out independently by Hryniuk (1987) and Tannock et al (1988) showed that an increased dose intensity is associated with a better response rate and an increased quality of life. These data have been partially confirmed, at least in terms of response rates, in several clinical investigations on MBC treated with EPI (Hortobagyi, 1990;French Epirubicin Study Group, 1991;Habeshaw et al, 1991;Marschner et al, 1994). For these reasons new regimens containing high-dose EPI have been developed with the aim of improving clinical results with acceptable toxicity (Hortobagyi, 1990;Ferguson et al, 1993;Marschner et al, 1994).…”
mentioning
confidence: 50%
“…On (Henderson et al, 1988;Tannock et al, 1988;Hortobagyi, 1990;Marschner et al, 1994). In fact, haematopoietic growth factors have been employed as rescue from myelosuppression with the aims of increasing the dose of antineoplastic drugs and also shortening the inter-cycle interval (Bronchud et al, 1989;O'Shaughness et al, 1990;Piccart, 1990;Ten Bokkel Huinink and Clavel, 1990;Habeshaw et al, 1991;Hoekman et al, 1991;Gebbia et al, 1994). The ORR achieved in this multicentre study was 72% (95% CL 66-78%) with a 25% complete response rate.…”
Section: Resuts Patient Populationmentioning
confidence: 88%
“…It has been suggested that dose intensity is one of the important factors regarding outcome in breast carcinoma. 16,[23][24][25] In our study, lower dose intensity of epirubicin and 5-FU, respectively, reflected significantly worse prognosis. Recent studies have indicated a dose-response correlation in the treatment of breast carcinoma, in both adjuvant and metastatic settings, which also has been demonstrated in the neoadjuvant setting for LABC.…”
Section: Discussionmentioning
confidence: 83%
“…All but one highlighted an advantage in terms of response rate in standard dose arms, but none of these assessed the true role of dose intensity. In fact, analysing data from three studies with more than 100 patients each, two (Tannock et al, 1988;Focan et al, 1990) did not report any data about total dose delivered, while in the third (Habeshaw et al, 1991), the significant increase in median dose intensity reported was associated with a significant increase in median total dose. A study conducted at the M.D.…”
Section: ~~~~~~~~~~~Discussion Doomentioning
confidence: 99%
“…Hryniuk and Bush (1991) first observed in a retrospective study the direct correlation between dose intensity and clinical outcome in advanced breast cancer. We are aware of at least 11 randomised trials that have prospectively explored the role of dose or dose intensity in advanced breast cancer (Tannock et al, 1988;Habeshaw et al, 1991;Carmo-Peirera et al, 1987;Hoogstraten et al, 1976;O'Bryan et al, 1977;Forastiere et al, 1982;Beretta et al, 1986;Hortobagyi et al, 1987;Ebbs et al, 1989;Becher et al, 1990;Focan et al, 1990). Seven of these, actually addressed the value of standard, or almost standard, doses of chemotherapy compared with low doses (Tannock et al, 1988;Habeshaw et al, 1991;Carmo-Peirera et al, 1987;Hoogstraten et al, 1976;O'Bryan et al, 1977;Forastiere et al, 1982;Focan et al, 1990).…”
Section: ~~~~~~~~~~~Discussion Doomentioning
confidence: 99%